Development Of Enhancing Horizontal Resolution (Ehr) Technique In 2-D Resistivity Survey - Muztaza, Nordiana Mohd (2013)
2-D resistivity method is an indirect method to the shallow subsurface survey for maintaining the geo-environment. It is used to measure the apparent resistivity of subsurface. The research involves modified 2-D resistivity acquisition technique using four different arrays (Wenner, Schlumberger, Wenner-Schlumberger and Pole-dipole). This technique is called Enhancing Horizontal Resolution (EHR). The EHR technique was developed in order to acquire detail and deeper penetration for shallow subsurface study. Four models were designed and validate to study the effectiveness of EHR technique which consists of one computer model using RES2DMOD software and three field models; miniature with original medium, bunker and underground drainages. Inversion model resistivity with common array shows less horizontal resolution compared to inversion model resistivity with EHR technique. Results from the EHR technique shows clear images of an anomalous and layers in terms of size, depth and resistivity value. Notably, the technique can perform the inversion on model data set efficiency and for archaeology, mineral exploration, engineering, environment and geology, the EHR technique employed. Eight different locations were identified which were mainly focused on shallow subsurface investigations. The locations are Lembah Bujang, Kedah; Bukit Bunuh, Lenggong, Perak; Pagoh, Batu Pahat, Johor; Batang Merbau, Tanah Merah, Kelantan; Puchong, Selangor; Putra Heights, Selangor; Nusajaya, Johor and Kaki Bukit, Perlis.